2007
DOI: 10.1111/j.1478-3231.2007.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contribution of major histocompatibility complex class II region to type 1 autoimmune hepatitis susceptibility in Venezuela

Abstract: In conclusion, our data indicate that type 1 AIH predisposition in a Venezuelan mestizo population of different ethnic backgrounds is associated with DRB1*1301 and DRB1*0301 alleles. In addition, our findings suggest that protection against disease might be conferred by the DQB1*04 allele, with distinct ethnic differences from other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
3
26
1
Order By: Relevance
“…Unlike the polymorphisms observed with HLA alleles conferring susceptibility for AIH-1 in mestizo Venezuelan patients [5], the genes polymorphisms evaluated in this study had no association with different age groups.…”
Section: Clinical Characteristics Of Patients and Their Possible Assocontrasting
confidence: 44%
See 2 more Smart Citations
“…Unlike the polymorphisms observed with HLA alleles conferring susceptibility for AIH-1 in mestizo Venezuelan patients [5], the genes polymorphisms evaluated in this study had no association with different age groups.…”
Section: Clinical Characteristics Of Patients and Their Possible Assocontrasting
confidence: 44%
“…It was decided to study these candidate genes as they influence T lymphocyte regulation which seems to be involved in the immunopathogenesis of AIH-1 [2]. It was also explored the association with HLA alleles previously described by our group in mestizo Venezuelan AIH-1patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk alleles were recently confirmed in a large genome-wide association study of northern Europeans [8]. However, the presence of DRB1*04:05 appears to increase the risk of AIH type 1 in Japanese and Chinese patients [9,10] and DRB1*13:01 in Venezuelan and Argentinian patients [11,12]. HLA associations in AIH type 2 are less studied, but indications of DRB1*03 and DRB1*07 increasing the risk of AIH type 2 are available [13].…”
Section: Introductionmentioning
confidence: 91%
“…In similar fashion, the haplotype Arg/Arg-Gln/ Glu haplotype appears to protect the Venezuelan Mestizo population from asthma and the haplotype Arg/Gly-Gln/ Gln haplotype appears to increase susceptibility. Probably, these differences are due to the mixture of our population, as demonstrated by the Fortes et al study 18 in which the Venezuelan Mestizo population with autoimmune hepatitis showed some disease-protective HLA alleles which differ from those reported for Caucasians and Japanese populations 18 . In several meta-analysis published [19][20][21][22] , the authors concluded that genetic polymorphisms of ADRβ2 do not represent an increased risk for developing asthma, yet are important in therapy outcome.…”
Section: Discussionmentioning
confidence: 71%